Growth, histochemical and physiological responses of non-edible oil producing plant (Reutealis trisperma) to gold mine tailings - MUHAMMAD HILMI; HAMIM HAMIM; YOHANA C. SULISTYANINGSIH; TAUFIKURAHMAN TAUFIKURAHMAN (Society for Indonesian Biodiversity, 2018)
Hilmi M, Hamim H, Sulistyaningsih YC, Taufikurahman. 2018. Growth, histochemical and physiological responses of non-edible oil producing plant (Reutealis trisperma) to gold mine tailings. Biodiversitas 19: 1294-1302. Reutealis trisperma (Blanco) Airy Shaw is a non-edible biodiesel producing plant that is able to grow well in various unfavorable environmental conditions. The study aimed to analyze the growth, physiological, and anatomical responses of R. trisperma to gold mine tailings. Three-month-old of R. trisperma were grown in 8 kg of polybags contained with mixed soil-compost medium treated with 0, 25, 50 and 100% of gold mine tailings for 3 months. Root and shoot growth, physiological and anatomical characters, and histochemical analysis of Pb inside the roots and leaves were examined. The root and shoot growth as well as chlorophyll a and b contents of R. trisperma grown in sole gold mine tailing at 100% significantly decreased, while at the lower concentration of gold mine tailings, the decrease of the growth performances was not significant, or even increased shown in that of 25% of tailing treatment. The treatment of gold mine tailing at 100% also induced lipid peroxidation, indicated by the significant increase in malondialdehyde (MDA) contents in the root as well as the leaves. Histochemical analysis showed that accumulation of Pb occurred both in roots as well as in leaves of R. trisperma treated with 100% of tailings. High-level tailing treatment also induced anatomical alteration in roots as well as leaves of the species. These results indicated that gold mine tailings induced oxidative stress in roots and leaves of R. trisperma resulted in growth inhibition.